2009
DOI: 10.1080/10934520902719894
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the photo-catalytic application of Fenton's reagent augmented with TiO2and ZnO for the mineralization of an oil-water emulsion

Abstract: 11 12In the present work, homogenous (photo-Fenton) and heterogeneous photo-assisted systems 13 (Fenton/TiO 2 /UV, Fenton/ZnO/UV and Fenton/TiO 2 /UV/Air) were investigated for the treatment of a 14 diesel-oil wastewater emulsion. The augmentation of the photo-Fenton process by heterogeneous TiO 2 15 increased the reaction rate, in terms of COD reduction efficiency from 61% to 71%. Furthermore, the 16 COD removal efficiency was increased to 84% when air was bubbled through the reactants. However, 17 if the Fen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Optimum values of the selected Table 7. This finding is in agreement with the previous observation of Tony et al [16] and Kositzi et al [22] for the treatment of wastewater. The optimal molar ratio H 2 O 2 : Fe +2 in the present study is 12 : 1; hence, the hydrogen peroxide is in excess.…”
Section: Optimization Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…Optimum values of the selected Table 7. This finding is in agreement with the previous observation of Tony et al [16] and Kositzi et al [22] for the treatment of wastewater. The optimal molar ratio H 2 O 2 : Fe +2 in the present study is 12 : 1; hence, the hydrogen peroxide is in excess.…”
Section: Optimization Analysissupporting
confidence: 83%
“…Among various AOPs, the Fenton reagent is one of the most effective methods for treating various industrial effluents including wastewater [13,14] and oily wastewater [15]. Previous work by the authors has involved the application of Fenton and the photo-Fenton reagents for the treatment of water polluted with diesel oil emulsion [10,16]. Although Fenton reagent has been reported extensively in the literature, there is a scarcity of publications focusing on its use for the treatment of car wash wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalyst of TiO2 with Fenton was applied by several previous studies to enhance oxidation of contaminants. Tony et al (2009) reported that a 71% and 84% COD removal were achieved at the natural pH by using Fenton/TiO2/UV and Fenton/TiO2/UV/air, respectively to treat the diesel oil-water emulsion while only 18% COD removal under same conditions was observed by the using Fenton/ZnO/UV. This result was attributed to the surface area of TiO2 was more than that for ZnO (Tony et al, 2009).…”
Section: Photocatalyst Of Tio2/fenton and Zno/fentonmentioning
confidence: 99%
“…In addition, Tony et al, (2009) reported that the presence of TiO2 is not only essential for the hydroxyl radicals (•OH) production, but also for the adsorption of the oil molecules on the TiO2 surface.…”
Section: Photocatalyst Of Tio2 Zno and Tio2/znomentioning
confidence: 99%
“…The degradation rate measured by COD and TOC increases as the TiO 2 concentration increases up to the optimum TiO 2 dosage in solar TiO 2 photocatalysis and solar photocatalysis using combined TiO 2 /Fenton processes, which were l g dm -3 and 0.66 g dm -3 , respectively. However, TiO 2 dosages greater than the maximum value have a negative effect on these processes since the excess TiO 2 particles increase the turbidity of the solution that decreases the penetration of light into the solution resulting in a reduction in production of hydroxyl radicals (•OH) at the TiO 2 surface [10].…”
Section: Effect Of Fenton Reagent and Tio 2 Concentrationmentioning
confidence: 99%